Perancangan Website Profil Sekolah Madrasah Tsanawiyah Negeri 2 Medan - Zulfikri Siregar, Ramli, Ika Sari (Pusdikra Publishing, 2021)
In Madrasah Tsanawiyah Negeri 2 Medan, the process of school profile information still uses brochures, pamphlets, banners and delivery through the students themselves so that the scope of promotion does not extend to other areas. To make it easy for the community to see the profile of the Mtsn 2 School and to make it easy for employees to input school profile information data, the authors designed a Web-based system. In the process of collecting data with the aim of solving problems, the authors used descriptive data collection methods, namely observation and interviews. Here the author uses a Web-based system. This website was developed using PHP and MYSQL software. This website contains the vision and mission, organizational structure, teacher data, employee data, academic, non-academic activity data and facility data. Which aims to introduce the Mtsn 2 Medan school to the general public. Based on the results of the tests that have been carried out, this Web-based school profile system can help Mtsn 2 Medan School in promoting the school to the wider community and is able to facilitate employee work